Design and development of iRemote Terminal Unit (iRTU) for undervoltage and overvoltage fault - Wan Nor Shela Ezwane, Wan Jusoh (2014)
Power outages is always happened and its take a longer time for fault detection, isolation and restoration. Existing RTU is very expensive because it needs to be imported. This problem affects the manufacturing sectors and having an impact on residential areas. Therefore, the design and development of the iRTU is implemented to ensure the problem of power outages can be detected immediately and the TNB can take action quickly. The purpose of this research is to design an iRTU hardware circuit board, develop the iRTU using software algorithms, create the interfacing for monitoring process and integrate software and hardware together to make the iRTU as a complete system. In order to ensure the iRTU system achieve its objectives, the methodology uses consists of OrCAD software to design and develop the iRTU circuit board, MPLAB software to program the microcontroller-base, Visual Basic software to create the GUI interfacing for the monitoring system and XBee as a communication media to connect iR TU to the control unit in short distances. The findings of this research show that the problem of power outages can be detected quickly by iRTU in the event of undervoltage and overvoltage faults and the signals will be sent to the control unit for further action. The importance of design and development of iRTU is being able to provide a system that can continuously collect, process, store data and operate independently through programming and save time and cost. The significance of this research is the improvement of the RTU system whereby the iRTU designed is based on existing RTUs. The iRTU has an industrial application potential which can be applied in TNB distribution automation and other industrial sectors to monitor weather, temperature, leakage current and others overcurrent. The proposed iRTU is to monitor the voltage fault and send the information in terms of type fault, the value of fault, substations status and locations, date and time to the monitoring unit.